WIDESPREAD ARC-RELATED MELTING IN THE MANTLE SECTION OF THE NORTHERN OMAN OPHIOLITE AS INFERRED FROM DETRITAL CHROMIAN SPINELS - Arai S.; Kadoshima K.; Morishita T. (My University, 2006)
We examined detrital chromian spinels, in recent river beds, derived from the mantle section to determine whether the mantle peridotite of the northern Oman ophiolite is of oceanic or arc origin. The Cr-number (=Cr/(Cr + Al) atomic ratio) of the detrital chromian spinels mostly ranges from 0.4 to 0.8, and more than 60% of them have Cr-numbers higher than 0.6. This indicates a significant extent of island-arc nature because chromian spinels seldom have Cr-numbers higher than 0.6 in ocean-floor rocks. The high-Cr-number (>0.6) spinels, which are also low in TiO2 (<0.3 wt%), are probably derived from an arc setting. Lherzolite with spinel Cr-numbers <0.2 is absent except near the base of the section. The high-Cr-number detrital chromian spinels are more abundant from the mantle section with more frequent discordant dunite pods. Post-deformational discordant dunite and adjacent harzburgite include the high-Cr-number spinels in outcrops. The upper mantle of the northern Oman ophiolite was formed at a fast-spreading ridge and was later modified by island-arc magmatism in a subduction-zone environment. This switch of tectonic setting from a mid-oceanic ridge to an island arc is essential in the explanation of obduction of a slice of oceanic lithosphere onto a continental margin as an ophiolite.